“Dosis de humus de lombriz y su respuesta en el rendimiento del cultivo de ají pimentón (capsicum annuum L.) variedad california en el fundo miraflores- banda de shilcayo San Martín-Perú” - Pinchi García, Anamelba (2008)
The present work of study "Oose earthworm humus and its answer in the yield of the cultivation of chili paprika (Capsicum annuum L.) Variety California", it was executed in the District of the Banda of Shilcayo, sector Ahuashiyacu property of the National University of San Martin - Tarapoto located at 3. 5 Km. of the city of Tarapoto. The objectives of this work were: 1) to determine the appropriate dose of fertilizing with earthworm humus in the production of paprika (Capsicum annuum L.) 2) to determine the relation benefit I cost of the evaluated treatments. The design used was of blocks totally at random (DBCA) with four (04), repetitions and five (05) treatments, three (03) of them with levels of organic fertilizing (earthworm humus 2, 4, 6 tons), one (01) chemical treatment N, P, K (200 - 100 - 100) and one (01) witness treatment without fertilizing, using 20 experimental units, distancing of the sowing was of O. 80 m between rows and O. 40 m among plants respectively. The treatment T3 (6 TM/Ha) it obtained the best result as for yield in TM/Ha reached a yield of 29, 31 TM/Ha respectively, it being superior to the other treatments that were applied earthworm humus anda chemical treatment nitrogen, phosphorus and potassium (NPK) that obtained good production but under the treatment indicated. Moreover the relation b/c had intervals of 4, 4 at 5, 2. All the treatments express relation b/c superior to the unit that it represent good values of profitability and is recommended to practice this activity to be profitable.